(untitled) (Applied Biological Research, 2020)
Ninety three genotypes of pigeonpea were evaluated in the Department of Pulses, TNAU, Coimbatore (India) on the basis of principal component analysis during kharif 2018-2019. The germplasms, including four checks, were subject to augmented completely randomized design (augmented design I) for evaluation. Of the 13 principal components identified, the first five principal components accounted for 75.21% of total variation among the genotypes studied. The first principal component analysis explained 25.88% variation which gradually reduced to 18.16% in PC2, 12.63% in PC3, 10.36% in PC4 and 8.17% in PC5. The cluster analysis based on 13 quantitative characters grouped all the genotypes into 5 main clusters. The cluster I, II, III, IV and V had 1, 2, 5, 7 and 78 genotypes, respectively. The study revealed that hybridization programme can be performed with elite genotypes viz., ICP 12057, ICP 8819, ICP 11124, IC 525463 and IC 525413 from different clusters to develop high yielding pigeonpea varieties.